Web-Based Assessment of the Phenomenology of Autobiographical Memories in Young and Older Adults - Manila Vannucci; Carlo Chiorri; Laura Favilli (Brain Sciences, 2021)
Autobiographical memories (ABMs) produce rich phenomenological experiences. Although few standardized and comprehensive measures of the phenomenology of ABMs have been developed, a web-based assessment of the full range of phenomenological properties is still missing. In the present study, we aimed to fill this gap and tested the psychometric properties of a web-based version of the Assessment of the Phenomenology of Autobiographical Memory (APAM) in a group of young and older adults. Specifically, taking advantage of the flexibility of web-based assessment methodology, we tested the rating consistency of APAM items, asking participants to rate the phenomenology of their ABMs with respect to seven cues, administered in one per day in seven different days. In each session, we also collected ratings of mood and arousal. Using linear mixed modeling (LMM), we could examine whether the phenomenology ratings differed with respect to age group while controlling for sex, age of the memory, arousal, mood, and specificity of the memory. Results revealed an adequate level of consistency of ratings in both young and older adults. Moreover, LMMs revealed a more intense experience of recollection and reliving (i.e., sensory and emotional) and a higher confidence in memory accuracy in older compared to younger adults. The theoretical and practical usefulness of a web-based assessment of the phenomenology of ABMs are discussed.